Ease-of-use protocol for the rapid detection of third-generation cephalosporin resistance in Enterobacteriaceae isolated from blood cultures using matrix-assisted laser desorption ionization–time-of-flight mass spectrometry. Issue 2 (June 2016) - Foschi, C.; Compri, M.; Smirnova, V.; Denicolò, A.; Nardini, P.; Tamburini, M.V.; Lombardo, D.; Landini, M.P.; Ambretti, S.
Summary: An ease-of-use protocol for the identification of resistance against third-generation cephalosporins in Enterobacteriaceae isolated from blood culture bottles was evaluated using matrix-assisted laser desorption ionization–time-of-flight mass spectrometry. A cefotaxime hydrolysis assay from chocolate agar subcultures using antibiotic discs and without inoculum standardization was developed for routine work flow, with minimal hands-on time. This assay showed good performance in distinguishing between cefotaxime-susceptible and cefotaxime-resistant strains, with excellent results for Escherichia coli (sensitivity 94.7%, specificity 100%). However, cefotaxime resistance was not detected reliably in Enterobacteriaceae expressing AmpC genes or carbapenemase-producing Klebsiella pneumoniae .